2007
DOI: 10.1158/1535-7163.mct-06-0039
|View full text |Cite
|
Sign up to set email alerts
|

HU-331, a novel cannabinoid-based anticancer topoisomerase II inhibitor

Abstract: Anthracyclines, a large group of quinonoid compounds, are used to treat some forms of cancer. Although highly effective in cancer therapy, the mechanism of action of these compounds is not specific; they act on cancer and other cells by numerous mechanisms. A new anticancer quinone (HU-331) was synthesized from cannabidiol. It shows significant high efficacy against human cancer cell lines in vitro and against in vivo tumor grafts in nude mice. In this study, we investigated its mode of action and present evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 36 publications
(25 reference statements)
2
52
0
Order By: Relevance
“…The BE colon carcinoma cell line has a point mutation and lacks DT-diaphorase [NAD(P)H:quinone oxidoreductase]; the HT-29 cell line is the same line but without the mutation. The two cell lines were affected by HU-331 to the same extent, which indicates that HU-331 does not act through one-electron reduction (Kogan et al, 2007). Apparently, the one-electron reduction of the quinone moiety in HU-331 is less effective than in doxorubicin, and this effect may be a further reason for the lack of cardiotoxicity of HU-331.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The BE colon carcinoma cell line has a point mutation and lacks DT-diaphorase [NAD(P)H:quinone oxidoreductase]; the HT-29 cell line is the same line but without the mutation. The two cell lines were affected by HU-331 to the same extent, which indicates that HU-331 does not act through one-electron reduction (Kogan et al, 2007). Apparently, the one-electron reduction of the quinone moiety in HU-331 is less effective than in doxorubicin, and this effect may be a further reason for the lack of cardiotoxicity of HU-331.…”
Section: Discussionmentioning
confidence: 91%
“…It is strongly antiangiogenic, both in vitro and in vivo (Kogan et al, 2006), making this compound a promising scaffold for new antiangiogenic drugs. It specifically inhibits topoisomerase II (Kogan et al, 2007). Here, we report that HU-331, although more active than doxorubicin in a HT-29 colon carcinoma model in nude mice and a Raji model in SCID-NOD mice, is significantly less cardiotoxic.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…According to Kogan et al (2006), HU-331 inhibits angiogenesis by directly inducing apoptosis of vascular endothelial cells without changing the expression of pro-and antiangiogenic factors and their receptors. In a subsequent study, HU-331 has been reported to mediate its antitumorigenic action mainly via inhibition of topoisomerase II (Kogan et al, 2007).…”
Section: N-(2-hydroxyethyl)-7z10z13z16z-docosatetraenamidementioning
confidence: 95%
“…The burgeoning literature on telomeres demonstrates that this field is intimately involved in pathways of both ageing and tumourigenesis. Key DNA repair enzymes topoisomerase II [7] and Rad51 have been shown to be inhibited by cannabinoids. Germ line chromosomal abnormalities in addition to MAPK stimulation constitute putative pathways of inheritable oncogenesis.…”
Section: Referencesmentioning
confidence: 99%